Growth Factors and COX2 Expression in Canine Perivascular Wall Tumors. (November 2015) - Avallone, G.; Stefanello, D.; Boracchi, P.; Ferrari, R.; Gelain, M. E.; Turin, L.; Tresoldi, E.; Roccabianca, P.
Canine perivascular wall tumors (PWTs) are a group of subcutaneous soft tissue sarcomas developing from vascular mural cells. Mural cells are involved in angiogenesis through a complex crosstalk with endothelial cells mediated by several growth factors and their receptors. The evaluation of their expression may have relevance since they may represent a therapeutic target in the control of canine PWTs. The expression of vascular endothelial growth factor (VEGF) and receptors VEGFR-I/II, basic fibroblast growth factor (bFGF) and receptor Flg, platelet-derived growth factor B (PDGFB) and receptor PDGFRβ, transforming growth factor β1 (TGFβ1) and receptors TGFβR-I/II, and cyclooxygenase 2 (COX2) was evaluated on frozen sections of 40 PWTs by immunohistochemistry and semiquantitatively scored to identify their potential role in PWT development. Statistical analysis was performed to analyze possible correlations between Ki67 labeling index and the expression of each molecule. Proteins of the VEGF-, PDGFB-, and bFGF-mediated pathways were highly expressed in 27 (67.5%), 30 (75%), and 19 (47.5%) of 40 PWTs, respectively. Proteins of the TGFβ1- and COX2-mediated pathways were highly expressed in 4 (10%) and 14 (35%) of 40 cases. Statistical analysis identified an association between VEGF and VEGFR-I/II ( P = .015 and .003, respectively), bFGF and Flg ( P = .038), bFGF and PDGFRβ ( P = .003), and between TGFβ1 and COX2 ( P = .006). These findings were consistent with the mechanisms that have been reported to play a role in angiogenesis and in tumor development. No association with Ki67 labeling index was found. VEGF-, PDGFB-, and bFGF-mediated pathways seem to have a key role in PWT development and growth. Blockade of tyrosine kinase receptors after surgery could represent a promising therapy with the aim to reduce the PWT relapse rate and prolong the time to relapse.